Постановка задачі моделювання розвитку трудових ресурсів у науковій сфері - Гришко, С. В.; Пересада, О. О. (ХНУРЭ, 2014)
Scientific personnel are part of the scientific and technical potential of the country. Therefore, the results of their development should be measured indicators of the country. In Ukraine, the growth of quantitative science does not lead to an improvement in quality of life. It is concluded that the need to develop new approaches to management science in Ukraine. To select the methodological approaches to modeling the development of scientific staff considered the concept of "development" and concluded that the need for dynamic modeling
Keywords: розвиток трудових ресурсів; ресурси у науковій сфері